The corrosion study on the effect of heat treated magnesium - manganese alloy for sacrificial anode cathodic protection - Mohd Hashahrin Firdaus Azri (School of Material Engineering, 2012)
These studies consist four phases of work which are chemical composition and physical properties of raw material, heat treatment process, electrochemical test and analysis of the results. The heat treatment conducted on commercial Mg anode and compared to its as-received and the pure Mg properties.